Karakteristik Mutu Nugget Tempe Selama Penyimpanan dengan Edible Film Pati Talas dan Sari Kunyit (Curcuma domestica val.) - Ariyanti, Kartika; Yurnalis; Rera Aga Salihat (Jurnal Research Ilmu Pertanian, 2022)
The purpose of the study was to determine the effect of storage time on the quality of tempeh nuggets with edible film packaging, taro starch and turmeric extract, and to find out how long the storage of tempeh nuggets resulted in damage. This study used a simple Completely Randomized Design (CRD) with 5 treatment levels and 3 replications. Observational data were analyzed using ANOVA and further test of DNMRT at 5% significance level. The treatment in this study was the storage time of tempeh nuggets with edible film packaging for 3, 6, 9, 12 and 15 days. The results showed that storage time had a significantly different effect on water content, ash content, protein content and fat content of tempe nuggets with edible film packaging. Storage of tempeh nuggets with edible film packaging was able to last up to day 12 (treatment D) with 13.93% water content, 1.95% ash content, 14.28% protein content, 18.62% fat content and organoleptic test values ​​at The 12th day showed that the tempeh nuggets had begun to experience changes in taste and texture.